PENGARUH PENERAPAN STRATEGI BELAJAR AKTIF TIPE TRADING PLACES TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI.IPA SMAN 1 V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Ferdila, Yogina - (Pendidikan Biologi, 2014)
This research was background by the low of studying biology result of student in SMAN 1 V Koto Kampung Dalam Kabupaten Padang Pariaman, which is caused by some factors like teacher who just only use speech method, studying is not interesting and bored lack of student interaction and not too active of student in studying. This research purpose to know the effect of implementing strategy studying active type trading places to the result of biology studying result of student in class XI .science SMAN 1 V Koto Kampung Dalam Kabupaten Padang Pariaman. The type this research is experiment research, by designing research Randomized Control Group Only Design. The population in this research is student of class XI. Science Semester II SMAN 1 V koto Kampung Dalam Kabupaten Padang Pariaman consist of 4 classes. The sampling taking technique which is done is using purposive sampling, so that gotten, class XI. Science 1 as experiment class and XI. Science 3 as control class. Based on data analysis gotten that the average of experiment class 78,02 with standard branching 7,09, meanwhile control class 71,14 wih standard branching 8,21. From data analysis t, gotten thitung(3,58). Ttable (1,66) so can be concluded that lesson with strategy implementing active studying trading places type can increase the result of studying biology class XI. Science SMA N 1 V Koto Kampung Dalam Kabupaten Padang Pariaman.